Between Family and Market: Poverty Among Women in a Social Welfare Program in Chile [Entre la Familia y el Mercado: Pobreza Femenina en Un Programa de Asistencia Social en Chile] - Calquin-Donoso, C (FLACSO Ecuador, 2023)
This study presents the results of qualitative and documentary research that aimed to explore the so-called problematization of poverty in the discursive corpus of the Chilean government welfare program Seguridades y Oportunidades. Modes in which poverty is constituted as a problem of governance were traced. A corpus that was elaborated by the government in the frame of the creation of this public policy was collected and analyzed, including presidential messages and debates among senators and deputies. The results indicate that the problematization of poverty is constituted through a discourse in which business rhetoric and conservative rhetoric articulate; thus, the problem is not rooted in the economic model but rather in the dependence of subjects on the state and, in the specific case of women, in the crisis of values and the family. What is the logical consequence? The proposal for an entrepreneurial subject enabled by the state to inhabit the entrepreneurial “forces of liberty” through a series of individualizing techniques like entrepreneurialism. It is concluded that the production of a government technology based on the cross of a fierce neoliberalism and a new social conservatism reproduces the classic sexual division of labor within an entrepreneurial scheme. © 2023 The authors.